Women Working as Traditional Prostitutes in Pakistan - Saeed, Fouzia (Review of Women's Studies; Vol 10 No 1-2 (2000): Review of Women's Studies Volume X, Numbers 1-2 (January-December 2000))
This is the product of an ethnographic study on the women working in prostitution in a traditional set-up in Shahi Mohallah, the most famous prostitution district in Pakistan, a certain district in the city of Lahore. Hardly any scientific study has been done on these women, and this study provides some basic information about them: their workplace, training for the job, work-related categories, articulation of self-image, aspirations, and plans for old age.